A comprehensive review on nitrate and phosphate removal and recovery from aqueous solutions by adsorption - Alemu Gizaw (IWA Publishing, 2021)
Nitrogen and phosphorus removal and recovery are considered as one of the interventions to control water bodies' eutrophication by application of various methods. Adsorption is an effective method for phosphate and nitrate removal from wastewater. It is efficient, quick, easy, low-cost and environmentally friendly. Even though different adsorbents have been developed with excellent properties, lack of compilation, lack of consistency in operational conditions, and lack of other important parameters used for direct comparison and practical use selection were observed. The first aim of this review is to provide facts and figures on novel adsorbents used for nitrate, phosphate, and simultaneous nitrate-phosphate removal and recovery. Second, various adsorbents applied for nitrate and phosphate removal have been compared in terms of the number of cycles that the adsorbent used; retained removal capacity (RR); the removal capacity of the adsorbent considering the threshold limit settled by EU and EPA as equilibrium concentration for phosphate (q0.1) and nitrate (q10); and time to reach the equilibrium capacity (t90). Third, based on the aforementioned criteria, the best adsorbents are proposed and this is the key novelty of this review work. Moreover, future aspects and challenges regarding nitrate and phosphate removal and recovery are presented. HIGHLIGHTS Reported novel nitrate, phosphate, and nitrate-phosphate co-adsorbents facts and figures were compiled.; The reported nitrate and phosphate recovery eluents used were assessed.; Adsorbents with nitrate and phosphate qm > 50 mg/g were shortlisted for comparison using q0.1/q10 (mg/g), t90 (h), number of cycles (cycles) and retained removal capacity (RR) as comparison parameters.; Relatively high removal capacity were proposed.;